Study Of The History Of Maternal Nutritional Status And Newborn Health On Toddler Nutrition Problems - Nenogasu, Yeri Delsia; Juwa, Maria Magdalena Mue (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Latar Belakang: Masalah Gizi balita menghambat perkembangan kognitif dan mengakibatkan penyakit kronis yang dapat berdampak pada kualitas hidup dikemudian hari. Faktor intrauterine seperti gizi ibu selama hamil, yang berdampak pada berat badan janin. Faktor ektrauterin seperti ASI ekslusif, pola asuh dan sanitasi lingkungan. Prevalensi masalah gizi seperti stunting di Provinsi NTT adalah yang tertinggi di Indonesia.Tujuan: Penelitian ini bertujuan untuk mengatahui dampak langsung dan tidak langsung status gizi ibu dan kesehatan bayi baru lahir terhadap masalah gizi balita. Metode Penelitian: Penelitian ini adalah penelitian analitik korelasional dengan pendekatan metode cross sectional. Kebenaran konsep teori yang dirumuskan diuji menggunakan Structural Equation Modeling (SEM) dengan pendekatan Partial Least Square (PLS) dengan aplikasi smart PLS 3.0.Hasil: Status gizi ibu signifikan memengaruhi kesehatan bayi baru lahir (T-statistic diatas rule of thumb yaitu 2,545). Kesehatan bayi baru lahir berdampak namun tidak signifikan memengaruhi masalah gizi balita (wasting) dengan nilai T-statistic diatas rule of thumb yaitu 1,081. Status gizi ibu berdampak namun tidak signifikan memengaruhi masalah gizi gizi balita (wasting) dengan nilai T-statistic diatas rule of thumb yaitu 0,131.Kesimpulan: Interaksi antara status gizi ibu (IMT dan Lila) berdampak positif 11,9% terhadap kesehatan bayi baru lahir dan secara bersamaan (status gizi ibu dan kesehatan baru lahir) berdampak positif 3% terhadap masalah gizi balita (wasting). Meningkatnya status gizi ibu (IMT dan Lila) sebelum hamil adalah akan meningkatkan kesehatan bayi baru lahir terutama berat badan lahir, panjang badan lahir dan lingkar kepala. Hal ini merupakan langkah penting sebagai upaya untuk mencegah kejadian wasting pada balita. Kata Kunci: Status gizi ibu, kesehatan bayi baru lahir, wasting ABSTRACT Introduction: Toddler nutrition problems hinder cognitive development and result in chronic diseases that can impact quality of life later in life. Intrauterine factors such as maternal nutrition during pregnancy, have an impact on fetal weight. External factors such as exclusive breastfeeding, parenting, and environmental sanitation. The prevalence of nutritional problems such as stunting in NTT Province is the highest in Indonesia.Purpose: This study aims to determine the direct and indirect impact of maternal nutritional status and newborn health on toddler nutrition problems. Methods: This research is a correlational analytical research with a cross-sectional method approach. The correctness of the formulated theoretical concepts was tested using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach with the application of smart PLS 3.0. Results: Maternal nutritional status significantly affected newborn health (T-statistic above rule of thumb of 2.545). Newborn health has an impact but does not significantly affect toddler nutrition problems (wasting) with a T-statistic value above the rule of thumb which is 1.081. Maternal nutritional status has an impact but does not significantly affect the nutritional problems of toddler nutrition (wasting) with a T-statistic value above the rule of thumb, which is 0.131. Conclusion: The interaction between maternal nutritional status (BMI and upper arm circumference) had a positive impact of 11.9% on newborn health and simultaneously (maternal nutritional status and newborn health) had a positive impact of 3% on toddler nutrition problems (wasting). Increasing the nutritional status of mothers (BMI and upper arm circumference) before pregnancy will improve the health of newborns, especially birth weight, birth length, and head circumference. This is an important step in an effort to prevent wasting events in toddlers. Advice: Conduct regular health checks before pregnancy, including nutritional status checks to identify maternal nutritional problems. Keywords: Maternal nutritional status, newborn health, wasting